Pengembangan Gim Edukasi Matematika Trigonometri “Trigo No Bouken” Berbasis Desktop - Yogie Sukandi Wijaya; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop an educational game as an alternative medium for learning mathematics in trigonometry, especially the special angle of trigonometry in sinus, co sinus, tangent, cosecant, secant and cotangent. This game was developed so users can use alternative media such as computer games to understand the special angles of trigonometry. The method used in this research is Game Development Life Cycle (GDLC). There are six stages of GDLC. They are initiation stage that discusses the concept of the game, pre-production stage that discusses the game design, production stage of the game development using Unity3D game engine, testing stage to test the game's functionality, beta testing stage for the user and release stage to release the game to public. The result of this study is a desktop-based educational game called